Within‐ and across‐breed imputation of high‐density genotypes in dairy and beef cattle from medium‐ and low‐density genotypes. (5th December 2013) - Berry, D.P.; McClure, M.C.; Mullen, M.P.
Summary The objective of this study was to evaluate, using three different genotype density panels, the accuracy of imputation from lower‐ to higher‐density genotypes in dairy and beef cattle. High‐density genotypes consisting of 777 962 single‐nucleotide polymorphisms (SNP) were available on 3122 animals comprised of 269, 196, 710, 234, 719, 730 and 264 Angus, Belgian Blue, Charolais, Hereford, Holstein‐Friesian, Limousin and Simmental bulls, respectively. Three different genotype densities were generated: low density (LD; 6501 autosomal SNPs), medium density (50K; 47 770 autosomal SNPs) and high density (HD; 735 151 autosomal SNPs). Imputation from lower‐ to higher‐density genotype platforms was undertaken within and across breeds exploiting population‐wide linkage disequilibrium. The mean allele concordance rate per breed from LD to HD when undertaken using a single breed or multiple breed reference population varied from 0.956 to 0.974 and from 0.947 to 0.967, respectively. The mean allele concordance rate per breed from 50K to HD when undertaken using a single breed or multiple breed reference population varied from 0.987 to 0.994 and from 0.987 to 0.993, respectively. The accuracy of imputation was generally greater when the reference population was solely comprised of the breed to be imputed compared to when the reference population comprised of multiple breeds, although the impact was less when imputing from 50K to HD compared to imputing from LD.